What have we learnt from targeted anti-TNF therapy?. (7th December 2009) - Feldmann, M; Williams, R O; Paleolog, E
Abstract : Anti-tumour necrosis factor (anti-TNF) therapy of patients with rheumatoid arthritis dates back to 1992, when the first proof-of-principle trials were performed in London by Maini and Feldmann. Considerable studies of the mechanism of action were performed, and insights into the way in which anti-TNF therapy delivers its benefit were obtained. In this brief review, certain aspects of knowledge acquired and the many gaps will be reviewed. Focus will be on the TNF-dependent cytokine cascade and what it means, and potential new approaches to treatment. Finally, an entertaining challenge: might many or even all unmet clinical needs be dealt with through cytokine analysis?